Face the facts – your organisation will be breached. Issue 8 (August 2016) - German, Paul
Abstract : It's simple: cyber-security isn't working. Too many companies are being breached and governments globally are recognising the need to invest heavily to protect vital services and infrastructure. When the most fiscally prudent UK Chancellor of the Exchequer in a generation stumps up an additional £1.9bn to combat the cyber-security threat, reality starts to bite – organisations of every size need to do more to safeguard operations. Today's defence in depth security models are naïve. The reliance on traditional access control, threat detection and threat protection is clearly inadequate. It is only by recognising that a breach has already occurred and containing that breach within a defined and secure segment that an organisation can avoid damaging system-wide breaches. Paul German of Certes Networks insists it is time to add another layer of defence – breach containment.